Klebsiella pneumoniae from Indonesian Tempeh were Genetically Different from that of Pathogenic Isolates - EVELINE AYU; ANTONIUS SUWANTO; TATI BARUS (Indonesian Society for microbiology, 2014)
Tempeh is important traditional Indonesian fermented food made from soybeans employing Rhizopus oligosporus or R. microsporus. During the process of tempeh production, some bacteria from the environment and tempeh starter become an integral part of tempeh, and even have important roles in determining the final quality of tempeh it self. Several studies reported the presence of Klebsiella pneumoniae in tempeh as one of vitamin B12 producing bacteria in tempeh. However, K. pneumoniae also known as opportunistic pathogens causing pneumonia and liver abscess in human. In this study, Enterobacterial Repetitive Intergenic Consensus-Polymerase Chain Reaction (ERIC-PCR) was employed to determine genetic diversity of K. pneumoniae isolated from tempeh and compared them with medical isolates. The result indicated that isolates from tempeh were genetically distinct from those of medical isolates.